Optimizing the pathology workstation "cockpit": Challenges and solutions - Elizabeth A Krupinski (Elsevier, 2010)
The 21 st century has brought numerous changes to the clinical reading (i.e., image or virtual pathology slide interpretation) environment of pathologists and it will continue to change even more dramatically as information and communication technologies (ICTs) become more widespread in the integrated healthcare enterprise. The extent to which these changes impact the practicing pathologist differ as a function of the technology under consideration, but digital "virtual slides" and the viewing of images on computer monitors instead of glass slides through a microscope clearly represents a significant change in the way that pathologists extract information from these images and render diagnostic decisions. One of the major challenges facing pathologists in this new era is how to best optimize the pathology workstation, the reading environment and the new and varied types of information available in order to ensure efficient and accurate processing of this information. Although workstations can be stand-alone units with images imported via external storage devices, this scenario is becoming less common as pathology departments connect to information highways within their hospitals and to external sites. Picture Archiving and Communications systems are no longer confined to radiology departments but are serving the entire integrated healthcare enterprise, including pathology. In radiology, the workstation is often referred to as the "cockpit" with a "digital dashboard" and the reading room as the "control room." Although pathology has yet to "go digital" to the extent that radiology has, lessons derived from radiology reading "cockpits" can be quite valuable in setting up the digital pathology reading room. In this article, we describe the concept of the digital dashboard and provide some recent examples of informatics-based applications that have been shown to improve the workflow and quality in digital reading environments.